Diseño e Implementación de un crossover de tres vías utilizando DSP con parámetros controlados por un dispositivo Android - Astudillo Amán, Darío Javier (2016)
The purpose of this Investigation Project is to implement a three crossover channel that enables to manipulate its cutoff frequencies wirelessly, through a device with an Android application. This crossover has three digital filters (low-pass, high-pass, band-pass) designed through FIR filters, implemented on microcontrollers with Digital Signal Processing functions (DSP) using windowing method. With Android interface is possible to manipulate cutoff frequencies from digital crossover, which permits to improve the system and remove undesired frequencies. Output signals can be listened through independent earphones or amplified speakers. Test done in this Project, such as communication, filters efficiency and microcontrollers processing speed, had shown that this electronic system accomplishes the planed objectives